Alzheimer's disease biomarker roadmap 2020: Time for tau: Strategic roadmap for the translation of tau biomarkers in the clinic: An international task force. (7th December 2020) - Dodich, Alessandra; Boccardi, Marina; Ashton, Nicholas J; Barthel, Henryk; Bischof, Gerard N.; Carrillo, Maria C.; Chiotis, Konstantinos; Corre, Julie; Démonet, Jean‐François; Drzezga, Alexander; Gietl, Anton F.; Hansson, Oskar; et al.
Abstract: Background: In the last decade, the research community has focused on defining reliable biomarkers for the early detection of the pathological hallmarks of Alzheimer's Disease (AD). In 2017, the Geneva AD Biomarker Roadmap Initiative adapted the framework for the systematic validation of oncological diagnostic biomarkers (Pepe et al., 2001) to AD, with the aim to accelerate their development and implementation in clinical practice (Frisoni et al., 2017). With this work we assess the maturity of tau biomarkers and we define the research priorities. Methods: In a two‐day workshop (Geneva, November 2019), we convened a panel of experts in AD biomarkers. The level of maturity for first and second generation tau PET tracers, CSF, and blood biomarkers was assessed based on the Biomarker Roadmap (Frisoni et al., 2017). Biomarker maturity and research priorities were processed by thematic subgroups before the meeting, and presented and discussed during the workshop. Results: Tau PET biomarkers showed partial evidence of analytical and clinical validity, particularly in their efficiency to distinguish AD dementia patients from healthy controls. First‐generation and second‐generation tracers showed different properties in terms of specific binding and accuracy in distinguishing AD from other neurodegenerative diseases. Plasma biomarkers showed promising achievements in analytical validity for p‐tau and Aβ42, while total tau was judged as unsuccessful by the experts. Compared to the recent introduction of tau PET and plasma, cerebrospinal fluid (CSF) biomarkers have been explored for decades in AD, and consistently they showed the highest level of maturity according to the strategic roadmap, with significant improvements compared to 2017, the development of fully automated assays being the most valuable. Research priorities consequently mainly concern analytical and clinical validity aims, with a main focus on covering assay definition and validation versus post‐mortem specimens. In view of studies on clinical utility, the definition of appropriate patient‐ and clinically‐relevant outcomes emerged as an urgent priority. Conclusions: Despite the recent development of PET‐ and plasma‐based tau biomarkers, both so far provide partial evidence for clinical validity. However, completion of studies on analytical validity is a key step required to properly investigate their clinical utility.